Social dialogue and collective bargaining in the civil aviation sector during the COVID-19 pandemic - Adam, Georg,Allinger, Bernadette (Publications Office of the European Union, 2022)
This report analyses the role of social dialogue and collective bargaining in addressing the challenges faced by the civil aviation sector during the COVID-19 pandemic. Social partner involvement in the measures introduced to mitigate the negative impacts of the pandemic varies across European countries. Social dialogue and collective bargaining played a prominent role in most countries, while in others they had a more limited role. The report also explores changes made to existing social dialogue and/or collective bargaining processes at national level. Although no substantial changes were identified in terms of social dialogue institutions and standard procedures, the study has shown that social dialogue dealt with issues beyond traditional employment and working conditions. Social partners were increasingly involved with emerging issues resulting from COVID-19, such as employment retention, including short-time work schemes, redundancies and maintaining the liquidity and solvency of companies.
10.2806/80520
Keywords: Graue Literatur; Amtliche Publikation; civil aviation; coronavirus disease; social dialogue; trade union; working conditions; social partners; labour relations; research report